2013
DOI: 10.1007/s11605-013-2253-y
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Consultation and Treatment of Patients with Hepatocellular Carcinoma Presenting to a Large Academic Medical Center in the US

Abstract: Background Management of hepatocellular carcinoma (HCC) often involves many subspecialist providers, as well as a broad range of treatment options. This study sought to evaluate referral and treatment patterns among patients with HCC at a large academic medical center. Methods Data from our cancer registry between 2003–2011 were abstracted on 394 patients who were primarily diagnosed/treated for HCC at Johns Hopkins Hospital (JHH); data on patients who were diagnosed/treated with HCC elsewhere and who receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
(27 reference statements)
0
17
0
Order By: Relevance
“…Furthermore, our group has documented variation in choice of therapy for patients with liver cancer and has demonstrated that receipt of therapy depends on a wide variety of factors, including clinical data as well as provider‐level and hospital‐level factors . In fact, even referral to a specialist varies considerably, with barriers to treatment preventing up to 50% of patients who have early stage disease from receiving potentially curative therapy …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our group has documented variation in choice of therapy for patients with liver cancer and has demonstrated that receipt of therapy depends on a wide variety of factors, including clinical data as well as provider‐level and hospital‐level factors . In fact, even referral to a specialist varies considerably, with barriers to treatment preventing up to 50% of patients who have early stage disease from receiving potentially curative therapy …”
Section: Discussionmentioning
confidence: 99%
“…Also, considerable variation in referral patterns, time to referral, and specific consultation teams exists across the country . Even within a single large academic institution, Stacy et al found no uniform pattern of referral for evaluation and treatment of patients newly diagnosed with HCC . Patient‐level factors impacting timeliness of referral as well as access to potentially curative therapy for HCC include age, disease stage, geographic area, and the underlying causes of cirrhosis—patients with ongoing substance abuse are not candidates for OLT and therefore may not be referred for evaluation at Type IV centers .…”
Section: Discussionmentioning
confidence: 99%
“…(15) Even within a single large academic institution, Stacy et al found no uniform pattern of referral for evaluation and treatment of patients newly diagnosed with HCC. (16) Patient-level factors impacting timeliness of referral as well as access to potentially curative therapy for HCC include age, disease stage, geographic area, and the underlying causes of cirrhosis-patients with ongoing substance abuse are not candidates for OLT and therefore may not be referred for evaluation at Type IV centers. (15,16) Other factors including insurance coverage, social support networks, race, and ethnicity also impact both the type of hospital in which patients are treated and the outcome following HCC diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the manage- Table 5. Changes in the laboratory data of the study group before and after interventions Original Article ment of HCC often involves many subspecialist providers (8). HCC patients require MDT management to select treatments according to tumor stage, performance status, and hepatic function (9).…”
Section: Discussionmentioning
confidence: 99%